From compound culture to benchmark culture : the transformation and development of BNBM - Liao, Hui, 1975- (SAGE Business Cases., 2017)
BNBM is a state owned Chinese enterprise that manufactures gypsum boards for the construction industry. The case examines the creation of ‘home culture' where BNBM cultivated a culture where the employees viewed the organization as their home.